2004
DOI: 10.1093/alcalc/agh127
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase Inhibitors for the Treatment of Wernicke–korsakoff Syndrome−three Further Cases Show Response to Donepezil

Abstract: Three patients diagnosed with Wernicke-Korsakoff syndrome were treated with the acetylcholinesterase inhibitor, donepezil, for periods of 6 to 8 months. Cognitive testing [Alzheimer's disease assessment scale-cognitive subscale (ADAS-Cog), Mini-mental state examination (MMSE), Clock drawing test and six item 2 min recall] and carer questionnaires [Informant Questionnaire (IQ Code), Neuropsychiatric inventory scale (NPI)] were performed at baseline, mid- and endpoint of the treatment period and post-discontinua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 14 publications
2
24
0
1
Order By: Relevance
“…Furthermore, our recent data demonstrated that when the hippocampal ACh levels are increased in the hippocampus by direct application of physostigmine, the behavioral impairment in spontaneous alternation in PTD rats is eliminated (unpublished data). Limited clinical trails have also revealed that anticholinesterase inhibitors improve cognitive functioning in patients with WKS [3,9]. Thus, although cholinergic dysfunction may be an over looked feature in thiamine deficiency-induced amnesia, increasing ACh levels does lead to significant behavioral recovery in the human disorder of WKS and the PTD model.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our recent data demonstrated that when the hippocampal ACh levels are increased in the hippocampus by direct application of physostigmine, the behavioral impairment in spontaneous alternation in PTD rats is eliminated (unpublished data). Limited clinical trails have also revealed that anticholinesterase inhibitors improve cognitive functioning in patients with WKS [3,9]. Thus, although cholinergic dysfunction may be an over looked feature in thiamine deficiency-induced amnesia, increasing ACh levels does lead to significant behavioral recovery in the human disorder of WKS and the PTD model.…”
Section: Discussionmentioning
confidence: 99%
“…AChE inhibitors (AChEIs) have also been suggested for other possible therapeutic applications, i.e. Wernicke-Korsakoff syndrome 10 and posttraumatic cognitive impairments 11 . Furthermore, besides of its cholinergic role, in the AD the AChE plays a non-cholinergic role accelerating beta-amyloid plaques assembly 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, chronic physostigmine administration in rats exposed to TD has been shown to reverse the impairment on an avoidance-learning task if started at an early phase of treatment (Nakagawasai et al, 2000). A limited number of case studies have revealed that WKS patients show improved cognitive abilities when given acetylcholinesterase inhibitors (Angunawela & Barker, 2001;Cochrane, Cochrane, Jauhar, & Ashton, 2005). These neurochemical as well as pharmacological data point towards the cholinergic system being involved in the learning and memory problems associated with thiamine deficiency and more generally diencephalic amnesia.…”
Section: Introductionmentioning
confidence: 99%